Experimental Study on Thermal Performance of a Bent Copper-Water Heat Pipe - Shuangshuang Miao; Jiajia Sui; Yulong Zhang; Feng Yao; Xiangdong Liu (International Journal of Aerospace Engineering)
Vapor-liquid phase change is regarded as an efficient cooling method for high-heat-flux electronic components. The copper-water bent heat pipes are particularly suited to the circumstances of confined space or misplaced heat and cold sources for high-heat-flux electronic components. In this paper, the steady and transient thermal performance of a bent copper-water heat pipe is studied based on a performance test system. The effects of cooling temperature, working conditions on the critical heat flux, and equivalent thermal conductivity have been examined and analyzed. Moreover, the influences of heat input and working conditions on the thermal response of a bent heat pipe have also been discussed. The results indicate that the critical heat flux is enhanced due to the increases in cooling temperature and the lengths of the evaporator and condenser. In addition, the critical heat flux is improved by extending the cooling length only when the operating temperature is higher than 50°C. The improvement on the equivalent thermal by increasing the heating length is more evident than that by increasing cooling length. It is also demonstrated by the experiment that the bent copper-water heat pipe can respond quickly to the variation of heat input and possesses superior transient heat transfer performance.